2021
DOI: 10.1038/s41419-021-03481-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch promotes hypertrophic scar formation through mechanically activated cation channel Piezo1

Abstract: Hypertrophic scar (HS) formation is a skin fibroproliferative disease that occurs following a cutaneous injury, leading to functional and cosmetic impairment. To date, few therapeutic treatments exhibit satisfactory outcomes. The mechanical force has been shown to be a key regulator of HS formation, but the underlying mechanism is not completely understood. The Piezo1 channel has been identified as a novel mechanically activated cation channel (MAC) and is reportedly capable of regulating force-mediated cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 69 publications
1
86
0
Order By: Relevance
“…CXCL1, as a neutrophil chemoattractant, induces sinusoidal thromboses, portal hypertension and fibrogenesis. In a recent study, increased Piezo1 expression was found in hypertrophic scars and was shown to participate in scar formation ( He et al, 2021 ).…”
Section: Cellular Mechanotransduction In Fibrosismentioning
confidence: 99%
“…CXCL1, as a neutrophil chemoattractant, induces sinusoidal thromboses, portal hypertension and fibrogenesis. In a recent study, increased Piezo1 expression was found in hypertrophic scars and was shown to participate in scar formation ( He et al, 2021 ).…”
Section: Cellular Mechanotransduction In Fibrosismentioning
confidence: 99%
“…This elevated Ca 2+ entry upon PIEZO1 activation is correlated with an increased Il-6 gene expression, p38 phosphorylation and TNC mRNA and protein expression, consistent with previous findings from our group [ 13 , 15 , 35 ]. Furthermore, PIEZO1-mediated Ca 2+ influx is involved in inflammatory pathways including the IL-6 receptor family and Ca 2+ -sensitive MAPK family such as p38 in various systems (e.g., renal fibrosis models, liver carcinoma cell lines or human dermal fibroblasts) [ 13 , 14 , 17 , 64 , 65 , 66 , 67 ]. IL-6 has been characterised as a key regulator of inflammation [ 68 , 69 , 70 ] and described as cardioprotective in the initial inflammatory response to cardiac pathology [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Piezo1 channel has been identified as a new mechanically activated cation channel (MAC) reportedly capable of modulating force-mediated cellular biological behavior. In hypertrophic scars, cycling mechanical stretching increased Piezo1 expression and promoted proliferation, migration, and differentiation of human skin fibroblasts and activated Piezo1-mediated influx of calcium ( He et al, 2021 ). Yan et al (2021 ) demonstrated phosphoproteome and biological evidence of abnormal calcium homeostasis and induction of abnormal platelet aggregation in keloid fibroblasts.…”
Section: Biomechanical Factors and Mechanotransduction Pathways In Ke...mentioning
confidence: 99%